Predicting the efficiency of photoswitches using force analysis - Neudecker, Tim; Dreuw, Andreas (The journal of physical chemistry letters, 2016)
Photoswitches convert light into mechanical energy by exerting forces on their environment during photoisomerization. However, the mechanical efficiency of this conversion is limited because a plethora of internal modes of the photoswitch do not contribute to the desired switching function but are also changed during the photoisomerization. Here we present a computational approach to quantify the efficiency of a photoswitch during the initial motion on the excited-state potential energy surface. We demonstrate the gist of our method by looking at the excited-state relaxation of carbon monoxide. Subsequently, the photoswitching efficiency of p-coumaric acid is analyzed as one representative example of the approach.
Gesehen am 30.11.2017